HAMBATAN KOMUNIKASI ANTAR PRIBADI ODHA (ORANG DENGAN HIV/AIDS) DALAM INTERAKSI SOSIAL DI LINGKUNGAN MASYARAKAT (Studi ODHA pada Yayasan PESONA Provinsi Bengkulu) - Indah Septirisani (UNIVED PRESS, Universitas Dehasen Bengkulu, 2021)
The purpose of this study was to identify and describe the barriers to interpersonal communication of people with HIV/AIDS in social interactions in the community. The method in this study used qualitative research methods. This research used the Symbolic Interaction Theory, the study of meaning in one's interactions. The researcher used informants based on the purposive sampling technique.The results of this study indicated that the barriers to interpersonal communication of people with HIV/AIDS in social interactions in the community are influenced by three factors: psychological barriers, mindset barriers, and cultural barriers. The existence of these three factors underlies the occurrence of bad stigma or discrimination against people with HIV/AIDS. People with HIV/AIDS in the communication process are conscious and reflective actors who unite objects they know through what they call self-identification. This means that the process of interpersonal communication has been running so far where a person with HIV/AIDS knows something, evaluates it, gives meaning and gives action in a social context.